2013
DOI: 10.1093/ndt/gft079
|View full text |Cite
|
Sign up to set email alerts
|

International survey of nephrologists' perceptions and attitudes about rewards and compensations for kidney donation

Abstract: We conclude that a minority of nephrologists favor rewards for donation, many agree with some compensation and a considerable majority favor donor health insurance. Perceptions of nephrologists about rewards and compensation are influenced by age, sex, urban versus rural location and geographic region of practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…In Ghahramani et al .‘s study,[5] 66% of the nephrologists agreed with this view. Rather than direct payment, other avenues of compensation have been spelt out by various researchers, such as medical leave and special donor insurance,[13] subsidized education, health, and other benefits.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Ghahramani et al .‘s study,[5] 66% of the nephrologists agreed with this view. Rather than direct payment, other avenues of compensation have been spelt out by various researchers, such as medical leave and special donor insurance,[13] subsidized education, health, and other benefits.…”
Section: Discussionmentioning
confidence: 91%
“…One study[11] found that family physicians in Mumbai feared that rich people would get priority for transplantation, echoing the sentiments expressed by the nephrologists in Ghahramani et al .‘s study,[5] where exploitation of the poor was a concern. In addition, two-third of the nephrologists were in favor of making kidney donation compulsory as it would save lives, the latter point being reiterated by Epstein.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[6][7][8][9] Besides, most studies have been carried out in developed countries, using quantitative approaches and focusing on knowledge and attitudes of health personnel. [10][11][12][13][14][15][16] This means that they provide no insight into how these professionals perceive, experience and act in this field.…”
Section: Salud Pública De México / Vol 59 No 1 Enero-febrero De 2017mentioning
confidence: 99%
“…A key question is whether organ donors think motivations to act altruistically will be jeopardized if financial rewards or payments are offered as incentives to donate organs, and whether they have an economic right to be compensated for costs incurred by the donative process. Public attitudes concerning payment for living kidney donation and the perspectives of healthcare professionals have been documented in relation to these questions, but the views of kidney donors themselves are rarely heard in the debates. Against criticism that the voices of patients or health consumers cannot count because they are too emotionally involved in their situation to see the issues clearly, we present data from qualitative sociological research documenting their perspectives.…”
Section: Introductionmentioning
confidence: 99%